Natural Regeneration in Sal (Shorear robusta Gaertn.F.) Forests: A Review - Savita; Gera, Neelu; Singh, Ombir (Indian Forester, 2017)
In this paper various factors responsible for absence of regeneration in Sal (Shorea robusta) forests have been discussed and some remedial measures like composition of species, management of middle-storey, shrub and herb layer, removal of allelopathic plants and others have also been suggested. In addition magnitude of insect pest incidence and their control measures has also been discussed. Natural regeneration, ecology and management of sal plantations have been described with some recommendations to manage the regeneration in these forests, which could be beneficial to the field forestry professionals in the country.